Assessment of nursing care quality in a cohort of neurological pa tients: cross sectional study - Nešić, Ivana; Matijević, Milijana (Nursing in the 21st Century, 2012)
ASSESSMENT OF NURSING CARE QUALITY IN A COHORT OF NEUROLOGICAL PA TIENTS: CROSS SECTIONAL STUDYIntroduction. High-quality nursing care is provided in accordance with the established standards and principles of the nursing profession. The quality of nursing care can be seen from the viewpoint of structure, process quality and quality outcomes.Aim. To estimate the level of nursing care in a cohort of patients hospitalized at the Neurology Clinic, Clinical Center of Serbia.Material and methods. The study design (cross sectional study) was conducted during December 2011. All patients (N = 107) , hospitalized at the six clinical departments: Department of Behavioral Disorders, Department of Neuromuscular Diseases, Department of Neurodegenerative Diseases, Department of Demyelinating Diseases, Department of Epilepsy and sleep disorders, were included in the research. Data was collected using targeted questionnaires and standardized scales: Glassgow, Braden, Morse and Barthel index. The assessment was done according to the level of nurturing. In analyzing the data, except for descriptive statistics, we used t-test and χ2 test, parametric and  nonparametric correlation analysis.Results. During the research in the clinics there were hospitalized 107 patients, 47 males and 60 females, average age 51.6 ± 15.7 years, with no statistically significant differences in relation to the type of clinical departments. Correlation with the type of clinical departments showed a statistically significant difference compared to the number of beds and number of patients (p = 0.001). Mean scores of all used scales are at the level of statistical significance: Glassgow scale p = 0.001, Bartel scale p=0.001, the Morse scale p = 0.034 and Braden Scale p=0.001. In relation to the number of nurses, we obtained a significant difference by type of department and shift-work schedule. The total number of nurses was significantly positively correlated with the Barthel index (r = 0238, p = 0.023). There was no significant correlation between the total number of nurses, patient age, and gender. Length of hospitalization was significantly negatively correlated with the Barthel index (r = 0409, p = 0.001), Braden scale (r = 0486, p = 0.001), skin lesions (r = 0318, p = 0.001), permanent catheter (r = 0.657, p = 0.001) and urinary tract infections (r = 0277, p = 0.004).Conclusions. The evaluation of the level of nursing care in a cohort of neurological patients indicates a high level of care, although the study results support deviation from the expected standard-number of nurses according to the level of care.